Analysis Research of Successing the SIGNAL Application in Batam City Using End User Computing Satisfaction (EUCS) Approach - Diny Anggraini Adnas; Red Dyson (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study aim of being able to assist application developers in improving the quality of systems and services in the SIGNAL application to be even better. This study used 2 methods which are quantitative with a minimum of 385 respondents from google from while qualitative on 30 people using interview techniques. The result shown that Content, Accuracy, Format, Ease of Use, and Timeliness variables positively influence the Satisfaction variable. This was supported by a coefficient of determination (R Square) of 79.1% for the quantitative data, and the comparison between the two quantitative and qualitative data sets demonstrated equivalence.